Diagnostico del infarto agudo de miocardio mediante las enzimas cardiacas. - Morales Chiriboga, Roxana Dayanara (2024)
Acute myocardial infarction is a direct complication of the cardiac muscle where cardiac enzymes are affected: CK MB and troponin T. The research project's objective was to analyze the cardiac enzymes most used in acute myocardial infarction by collecting information on a scientific basis, followed by its clinical manifestations and enzymatic laboratory diagnostic methods. It is a descriptive, documentary, non-experimental, retrospective study where 68 scientific articles were reviewed, and 37 articles were selected by applying inclusion and exclusion criteria. The information was reported in scientific databases such as PubMed, Scielo, Dialnet, Redalyc, Elsevier, and Google Scholar. With the analysis and discussion of several authors, it was possible to conclude the research proposal and the objectives set; it is evident that cardiac enzymes are of great help in the diagnosis of acute myocardial infarction, showing the effectiveness of detection at the beginning of the clinical picture where it acts primarily. The enzyme CK-MB indicates the presence of a lesion, while Troponin T suggests the presence of a lesion. As for the most frequent signs and symptoms, dyspnea, chest pain that in turn radiates to the upper limbs, neck, and jaw, as well as nausea and fatigue, were found. Electrochemiluminescence is the enzymatic method most used for detecting acute myocardial infarction because it has high sensitivity and specificity, according to the commercial company Roche.